The Main Trends and Principles of Modern Linguistics - Valentina Avraamovna Maslova (Russian Language Studies, 2018)
The article identifies and describes the main trends and principles of modern linguistics such as integrativity, anthropocentricity, communicativeness, dialogicness, discursiveness, culturecentricity, interest in deep language knowledge, which interact even in one research. Taking the human factor into account is the most important characteristic of post-nonclassical science, and therefore the anthropocentric vector of modern linguistic research contributes to the emergence of most of these principles. In the twenty-first century, all humanities including linguistics are changing under the new demands of the modern social situation: first of all, due to a higher level of synthesis of humanities, their integrativity not only among themselves, but also with natural sciences. For such a complex research object as language, representatives of many sciences can contribute - from molecular biology, genetics, neurophysiology and psychology to anthropology, neurolinguistics and analytical philosophy. Research specialization should be found, as V.I. Vernadsky points out, “not in science, but in problems”, because the removal of information barriers between the sciences gives a powerful impetus for the research development. Thanks to these tendencies and principles, linguistics started exploring the problems that previously were not part in its sphere of interest. Now the sphere of interest of linguistics includes everything that meets the requirements of sign systems theory and allows to see the deep semantic foundations of language, human mentality and culture.